Microbiological Quality of Probiotic Products - Zavišić, Gordana; Ristić, Slavica; Petković, Branka; Živkov Šaponja, Dragoslava; Jojić, Nikola; Janković, Drina (Archives of Pharmacy, 2023)
Microorganisms used as probiotics should meet elementary safety aspects (non-toxicity, absence of antibiotic resistance genes and translocation) and functional/technological aspects (resistance and survival in the acid gastric environment, adhesiveness, stability, and cell viability). Probiotics with the health claim of being a dietary product or a pharmabiotic (drug category) should be clinically tested, validated, documented, and continuously controlled for quality. Important quality parameters include the identification of declared probiotic strains, the number of viable microorganisms (probiotic bacteria and/or fungi), and microbiological purity (absence of specified pathogenic/opportunistic pathogenic bacteria and fungi, and limitation of total unspecified contaminants such as aerobic bacteria, yeasts, and molds). Due to numerous reports of low-quality commercial probiotics marketed for human use, this review discusses the methods used to test the probiotic microorganism content, safety for the intended use, and proven health benefits of those probiotics whose microbiological quality deviates from the manufacturer’s stated content, as well as the maintenance of cell viability, i.e., stability of the probiotic during the shelf life. In addition, the adverse effects of probiotics and the potential hazards to the health of the user are addressed.
Keywords: probiotic; microbiological quality; safety; stability